Metabolic engineering of Methylobacterium extorquens AM1 for the production of butadiene precursor - Yang, Jing (Microb Cell Fact, 2018)
BACKGROUND: Butadiene is a platform chemical used as an industrial feedstock for the manufacture of automobile tires, synthetic resins, latex and engineering plastics. Currently, butadiene is predominantly synthesized as a byproduct of ethylene production from non-renewable petroleum resources. Although the idea of biological synthesis of butadiene from sugars has been discussed in the literature, success for that goal has so far not been reported. As a model system for methanol assimilation, Methylobacterium extorquens AM1 can produce several unique metabolic intermediates for the production of value-added chemicals, including crotonyl-CoA as a potential precursor for butadiene synthesis. RESULTS: In this work, we focused on constructing a metabolic pathway to convert crotonyl-CoA into crotyl diphosphate, a direct precursor of butadiene. The engineered pathway consists of three identified enzymes, a hydroxyethylthiazole kinase (THK) from Escherichia coli, an isopentenyl phosphate kinase (IPK) from Methanothermobacter thermautotrophicus and an aldehyde/alcohol dehydrogenase (ADHE2) from Clostridium acetobutylicum. The K(m) and k(cat) of THK, IPK and ADHE2 were determined as 8.35 mM and 1.24 s(−1), 1.28 mM and 153.14 s(−1), and 2.34 mM and 1.15 s(−1) towards crotonol, crotyl monophosphate and crotonyl-CoA, respectively. Then, the activity of one of rate-limiting enzymes, THK, was optimized by random mutagenesis coupled with a developed high-throughput screening colorimetric assay. The resulting variant (THK(M82V)) isolated from over 3000 colonies showed 8.6-fold higher activity than wild-type, which helped increase the titer of crotyl diphosphate to 0.76 mM, corresponding to a 7.6% conversion from crotonol in the one-pot in vitro reaction. Overexpression of native ADHE2, IPK with THK(M82V) under a strong promoter mxaF in M. extorquens AM1 did not produce crotyl diphosphate from crotonyl-CoA, but the engineered strain did generate 0.60 μg/mL of intracellular crotyl diphosphate from exogenously supplied crotonol at mid-exponential phase. CONCLUSIONS: These results represent the first step in producing a butadiene precursor in recombinant M. extorquens AM1. It not only demonstrates the feasibility of converting crotonol to key intermediates for butadiene biosynthesis, it also suggests future directions for improving catalytic efficiency of aldehyde/alcohol dehydrogenase to produce butadiene precursor from methanol. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12934-018-1042-4) contains supplementary material, which is available to authorized users.